The Influence Of Mental Health Literacy On The Stigma Of Mental Disorders Among Nursing Students - Sri Wulan Lindasari; Reni Nuryani; Nunung Siti Sukaesih; Rizka Salsabila (Jurnal Ners, 2026)
The number of people with mental disorders in Indonesia continues to increase significantly from year to year. This is exacerbated by the high stigma against people with mental disorders in society, including among students. This negative stigma attached to people with mental disorders requires education by promoting mental health literacy. Therefore, this study aims to determine the effect of mental health literacy on the stigma of people with mental disorders among students in the Nursing Study Program at UPI Sumedang Campus. The method used in this study is descriptive correlation. The population in this study was all nursing students, totaling 512 people. The sampling technique used was total sampling. Data collection tools used were the Mental Health Literacy Scale (MHLS) questionnaire to measure mental health literacy and the CAMI (Community Attitudes towards Mental Illness) questionnaire to measure stigma against people with mental disorders. The results of the study found that almost the majority (80.9%) of mental health literacy levels in nursing students were in the high category, almost the majority (85.5%) of nursing students experienced non-stigmatic behavior towards people with mental disorders and there was a relationship between mental health literacy and the stigma of people with mental disorders in nursing students with a P value = 0.02 and a correlation value of 0.763. So it is very important to carry out health promotion to prevent stigmatization in people with mental disorders